4‐Mercaptobenzoic acid‐assisted laser desorption/ionization mass spectrometry for sensitive quantification of cesium and strontium in drinking water. (7th July 2022) - Shao, Wenya; Sun, Ying; Su, Hang; Sun, Qianqian; Lin, Zian
Abstract : Rationale: Cesium ions (Cs + ) and strontium ions (Sr 2+ ), which enter the human body mainly through drinking water, are an important determinant of health. They are widely distributed on Earth and extremely soluble in water. In order to assist assessment of the drinking safety, it was essential to develop a rapid analytical method for quantification. We have established a 4‐mercaptobenzoic acid (MBA)‐based matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS) method for the rapid detection and sensitive quantification of Cs + and Sr 2+ in the aqueous environment. Methods: Using MBA as the matrix, the rapid detection and quantification for Cs + and Sr 2+ were conducted by MALDI‐TOF‐MS. At first, the concentration of MBA was optimized. Then, salt tolerance, detection limit and reproducibility of this method were evaluated by standard solutions. Finally, the calibration curves were constructed and applied to the rapid determination of Cs + and Sr 2+ in six commercially available bottled waters for drinking. Results: For the MBA‐assisted MALDI‐TOF‐MS method, the optimal concentration of MBA was 2 mg/mL. The signal‐to‐noise (S/N) ratio of Cs + was up to 971 in 1000 mmol/mL NaCl solution. The detection limits of the method for Cs + and Sr 2+ were 3 pg/mL and 10 pg/mL, respectively. Furthermore, this developed method was applied to the rapid analysis of Cs + and Sr 2+ in six commercially available drinking waters, and the results correlated well with the results obtained from a validated inductively coupled plasma mass spectrometry (ICP‐MS) method. Conclusions: The MBA‐assisted MALDI‐TOF‐MS method has high sensitivity, fast detection speed, less background interference, and high reproducibility in the analysis of Cs + and Sr 2+ . Because of the physiological functions and general toxic effects, detection of Cs + and Sr 2+ in water is of major importance for drinking safety.